Xét (a,b)[a,b] = a.b
=>(a,b) = 360 : 6 = 6
Gọi a = 6m; b = 6n và (m,n) = 1
Khi đó, a.b = 62.mn
=>m.n = 360 : 62 = 10
Ta chọn 2 số m và n có tích là 10 và (m,n) = 1
m | 1 | 2 | 5 | 10 |
n | 10 | 5 | 2 | 1 |
a | 6 | 12 | 30 | 60 |
b | 60 | 30 | 12 | 6 |
Ta có: ab = [a,b].(a,b)
=> (a,b) = 360 : 60
=> (a,b) = 6
Vì (a,b) = 6 => a = 6m, b = 6n (m,n thuộc N; (m,n) = 1)
Lại có: ab = 360
=> 6m.6n = 360
=> 36mn = 360
=> mn = 10
Vì a < b => m < n
Mà (m,n) = 1
Ta có bảng :
m | 1 | 2 | 5 | 10 |
n | 10 | 5 | 2 | 1 |
a | 6 | 12 | 30 | 60 |
b | 60 | 30 | 12 | 6 |
Vậy...